Prevalence of Menstrual Irregularities in Psychiatric Patients and Its Impact on Treatment Adherence: A Cross-Sectional Study - Pooja Shakya; Poulami Basu; Rupam Kumari; Manoj Kumar (BJPsych Open)
Aims: Menstrual irregularities (MI) are a frequently overlooked yet clinically significant concern among women with psychiatric disorders. Several psychiatric conditions, particularly schizophrenia and bipolar disorder, involve dopaminergic dysregulation, which may contribute to hormonal disturbances. Antipsychotic medications, especially typical antipsychotics, are known to impact menstrual cycles through their effects on dopamine pathways, leading to hyperprolactinemia and subsequent menstrual dysfunction. However, research on the prevalence of MI and its relationship with psychiatric illness and treatment adherence remains limited, particularly in the Indian context. This study aims to assess the prevalence of MI among female psychiatric inpatients and explore its association with socio-clinical factors, antipsychotic medication use, and treatment adherence.